THE IMPACT OF BODY LANGUAGE USED BY ARABIC TEACHERS ON THE DEVELOPMENT OF LANGUAGE PERFORMANCE IN ARABIC SCHOOLS/ Ø£Ø«Ø± Ø§Ø³ØªØ®Ø¯Ø§Ù… Ù…Ø¹Ù„Ù…ÙŠ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¥ÙŠÙ…Ø§Ø¡Ø§Øª Ø§Ù„ÙˆØ¬Ù‡ ÙÙŠ ØªÙ†Ù…ÙŠØ© Ø§Ù„ØªØØµÙŠÙ„ Ø§Ù„Ù„ØºÙˆÙŠ ÙÙŠ Ø§Ù„Ù…Ø¯Ø§Ø±Ø³ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Ibrahim, Sani Muhammadu; Muhammad, Ashiru (Ijaz Arabi Journal of Arabic Learning, 2019)
This article aimed at findings the impact of body language used by Arabic teacher on developing language performance of Arabic students. To justify the objectives of the article, the researchers stated one question and attempt was made to answer it. Senior Arabic Schools II in Kaduna State were used as a population of the study, quasi-experimental design was used for the research purposes. The sample of 80 students was drown from the population. They were further subdivided into two experimental group with (40) and control group (40) students, purposive sampling technique was employed in the sampling. Â The researchers designed questions derived from Arabic Grammar, Arabic liteary texts and Rhetorics to test the performance of the students. The results show that there is positive effect of body language used by Arabic teacher on developing language performance. Based on the research finding, the researchers recommend that Arabic teachers in Senior Arabic schools should use body language appropriately in order to develop studentsâ€™ language performance. Also, National Board for Arabic and Islamic Studies, should train the Arabic teachers on the body language skills and the ways in which these skills can be used appropriately used during teaching.